STUDI PENGARUH ALUMINIZING TERHADAP PEMBENTUKAN DIE SOLDERING - Andaru .; Dody Prayitno; Eni Pujiasturi (JURNAL PENELITIAN DAN KARYA ILMIAH LEMBAGA PENELITIAN UNIVERSITAS TRISAKTI, 2016)
A mould in die casting industri has a problem like a die soldering. The die soldering due to a molten aluminium stick on a mould surface and hold on although a casting produk has been rejected. Removing the die soldering need cost and time. So the mouldshoul be protected from the die soldering. In this research, an aluminizing process is used as an alternatif method to protect the mould from die soldering defect. The hot dip aluminizing process increases the corrosion resistance of steel. The aim of reseach is to answer the question “Do the hot dip aluminizing process (Al-53%Cu) protect a mould steel from the die soldering?”. Researchmethodologi. First, the steel samples as assumed as a steel mould are immersed into molten of Al-53%Cu (750 oC) for 3 minutes. Secondly a molten aluminium (700 oC) is poured onto the aluminized steel mouldsamples .it is called as a die casting simulation. The results. The hot dip aluminizing (Al-53%Cu) process at 700 oC can not protect the steel mould surface from the die soldering.